PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN PEMBELIAN DI ANGKRINGAN PEMUDA KNPI - Sukimin Sukimin; Eva Fidriani; Nina Indriastuty (Jurnal GeoEkonomi, 2023)
This study aims to analyze the effect of simultaneously and partially the variables of Product, Price, Place, Promotion, Person/Actor, Process and Physical Evidence on Purchase Decisions at KNPI Youth Angkringan Balikpapan. The type of research used is expanatory quantitative research. The number of samples in this study was 177 consumers of the Balikpapan KNPI Youth Angkringan. The sampling technique used in this research is probability sampling and simple random sampling method. Analysis of the data used is descriptive analysis and multiple linear regression analysis. The test tools used are instrument test, classical assumption test, and hypothesis testing. The results of this study indicate that the products, prices, places, promotions, people/actors, processes and physical evidence in the company are good so that purchasing decisions increase. The results of multiple linear analysis show that simultaneously and partially these variables have a positive and significant influence on purchasing decisions